Identificación de nematodos gastrointestinales con importancia zoonótica en muestras fecales de perros tomadas en tres mercados del suroeste de la ciudad de Guayaquil - Benalcázar Bone, Gabriela Mischell (2018)
The present work consisted in determining the presence of zoonotic gastrointestinal nematodes: Ancylostoma caninum, Toxocara canis and Trichuris vulpis in faecal samples of canines taken inside and outside the Santa Teresita, Gómez Rendón and Suburban Battalion markets located in the southwest of the city of Guayaquil, which was carried out by means of flotation laboratory methods and direct smear. It was determined that the Santa Teresita market is one of the markets in which there is less presence of these parasites, in addition there was no case of coinfection in any of the sampled markets; One of the specific objectives was to determine the presence of the aforementioned parasites by means of two diagnostic methods, for which 30 fecal samples were examined, of which 49 por cientop were positive for Ancylostoma caninum, 43 por ciento tested positive for Toxocara canis and 8 por ciento tested positive for Trichuris vulpis. Another specific objective was to evaluate through epidemiological surveys if there is a relationship between the parameters included in surveys, diarrheas and markets; for which 205 surveys were made to all the people who frequent the three markets mentioned above; It was determined that the people who most frequently take their pets to the veterinarian have a lower probability of presenting diarrhea (p value of 0.026), in turn all those people who do not disinfect fruits and vegetables have a higher risk of presenting diarrhea as well as all the people who allow that your pets defecate outside the home (p value of 0.003); It was finally determined that people who do not have the habit of washing their hands frequently or do not do it properly are more likely to have diarrhea (p value of 0.035).